2007
DOI: 10.1152/japplphysiol.00056.2007
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycan fragmentation and respiratory mechanics in mechanically ventilated healthy rats

Abstract: This research investigated whether stretching of lung tissue due to increased positive alveolar pressure swings during mechanical ventilation (MV) at various tidal volumes (V(T)) might affect the composition and/or structure of the glycosaminoglycan (GAG) components of pulmonary extracellular proteoglycans. Experiments were performed in 30 healthy rats: 1) anesthetized and immediately killed (controls, C-0); 2) anesthetized and spontaneously breathing for 4 h (C-4h); and 3) anesthetized, paralyzed, and mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
47
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 38 publications
11
47
0
5
Order By: Relevance
“…This fact confirms the tendency of OLV is prone to the occurrence of acute lung injury in spontaneous breathing subjects [14], reinforced by evidence that near physiologic tidal volumes may also be somehow harmful [17].…”
Section: Discussionsupporting
confidence: 72%
“…This fact confirms the tendency of OLV is prone to the occurrence of acute lung injury in spontaneous breathing subjects [14], reinforced by evidence that near physiologic tidal volumes may also be somehow harmful [17].…”
Section: Discussionsupporting
confidence: 72%
“…Some authors have shown that ventilation under physiologic tidal volumes (6-8 ml/kg) for a few hours induces proteoglycan fragmentation from the alveolar septa, which is not associated with activation of systemic or tissue MMPs, lung edema, inflammation, or collagen fiber deposition [2,6].…”
Section: The Ecm During Mechanical Ventilationmentioning
confidence: 99%
“…On the other hand, Al Jamal et al showed that extremely high VT (30 ml/kg) and high respiratory rate (90 breaths/minute) induce the expression of versican (CS-PG), basement membrane HS-proteoglycan (HS-PG), and biglycan in lung tissue [16]. Moriondo et al also observed CS and HS fragmentation at high VT [6] and showed that the fluid overload associated with high-VT mechanical ventilation worsened GAG fragmentation, mainly in the ventral lung regions [13].…”
Section: The Ecm and Ventilator-induced Lung Injurymentioning
confidence: 99%
See 2 more Smart Citations